Experiences With Health Care Services in Switzerland Among Immigrant Women With Chronic Illnesses - Frahsa, Annika; Farquet, Romaine; Bayram, Tevfik; De Araujo, Luna; Meyer, Sophie; Sakarya, Sibel; Cattacin, Sandro; Abel, Thomas (Frontiers in Public Health, 2020)
Introduction: Descriptive data indicate a high burden of chronic illness among immigrant women in Switzerland. Little is known about how immigrant women with chronic illnesses experience healthcare services. This paper presents a methodological approach theoretically informed by Sen’s capability approach and Levesque’s framework of access to healthcare to study patient-reported experiences (PREs) of Swiss healthcare services among immigrant women with chronic conditions. Methods: We conducted 48 semi-structured qualitative interviews in Bern and Geneva with Turkish (n=12), Portuguese (n=12), German (n=12), and Swiss (n=12) women. Participants were heterogenous in age, length of stay, SES, and educational attainment, illness types and history. We also conducted semi-structured interviews with healthcare and social service providers (n=12). Interviewed women participated in two focus group discussions (n=15). Interviews were transcribed verbatim and analysed using Atlas.ti software, based on Gale et al.’s framework approach. Findings informed three stakeholder dialogues in which women as well as healthcare providers and policymakers from various territorial levels participated. Results: Our methodological approach succeeded in integrating women’s perspectives—from initial data collection in interviews to identify issues, focus group discussions to increase rigor, and stakeholder dialogues to develop tailored recommendations based on PREs. Discussion: This is one of the first studies in Switzerland that used PREs to research healthcare services and healthcare needs among immigrant women with chronic illnesses. This paper provides new insights on how to better understand existing challenges and potentially improve access to and quality of care.